2005
DOI: 10.1159/000089246
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Effective Regimen for Prevention of Radial Artery Spasm during Coronary Catheterization

Abstract: Radial artery spasm occurs frequently during the transradial approach for coronary catheterization. Premedications with nitroglycerin and verapamil have been documented to be effective in preventing radial spasms. Verapamil is relatively contraindicated for some patients with left ventricular dysfunction, hypotension and bradycardia. We would like to know whether nitroglycerin alone is sufficient for the prevention of radial artery spasm. We conducted a randomized controlled trial to compare the spasmolytic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 47 publications
2
74
1
5
Order By: Relevance
“…Combinations of different drugs were also evaluated in several studies [15,16,[18][19][20] combining agents offered no advantage. The best studied combination of verapamil and A C C E P T E D M A N U S C R I P T…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combinations of different drugs were also evaluated in several studies [15,16,[18][19][20] combining agents offered no advantage. The best studied combination of verapamil and A C C E P T E D M A N U S C R I P T…”
Section: Resultsmentioning
confidence: 99%
“…nitroglycerin was evaluated in 5 studies [16,17,[22][23][24]. The pooled results of these studies yielded 21% RAS rate (5 studies, 135/630) however, two studies [17,23] reported unusually high rates of RAS (71% and 52% respectively) and differed from the other studies because the verapamil dose was low (100 µg).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The majority of previous reports advocated the use of intra-arterial vasodilators, most frequently verapamil and/or nitrogylcerin [7,8,17,18]. In a head-to-head comparison study between nitroglycerin and verapamil there was no statistically significant difference in the ACEI -angiotensin converting enzyme inhibitor; BP -blood pressure; HDL-C -high-density lipoprotein-cholesterol; LDL-C -low-density lipoprotein-cholesterol; RAS -radial artery spasm incidence of RAS [22]. Furthermore, a recent study indicated that beyond the learning curve preventive administration of intra-arterial verapamil offers no advantage over ad hoc application in terms of access site conversion rates [23].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the limited literature found studies with small sample sizes and inconsistent dosing of verapamil in radial cocktails. Chen et al 4 studied the use of a lower dose (1.25 mg) of verapamil in more than 400 patients and determined that the verapamil dose could be decreased from 2.5 mg and still signifi cantly prevent radial artery spasm. At this time, OSUWMC made the decision to change the verapamil dose in the syringe to 1 mg, which would allow 5 syringes to be made from a 2.5 mg/mL, 2 mL vial instead of just 2 syringes; this further conserved the manufacturer supply.…”
Section: Verapamil Shortage Issuedmentioning
confidence: 99%
“…There is no standard defi nition for radial artery spasm and there are differences in techniques used to perform the procedure, but the incidence of vasospasm is estimated to be between 2% and 51.3%. [1][2][3][4] Factors other than radial artery spasm can lead to the procedure being stopped or the access site being changed, so the incidence attributable to radial artery spasm alone is not well-established.…”
mentioning
confidence: 99%